Plato and a platypus walk into a bar-- : understanding philosophy through jokes - Cathcart, Thomas, 1940-; Klein, Daniel M. (New York : Penguin Books, 2008)
A collection of jokes, vaudeville humor, cartoons, and limericks that offer insight into the basic concepts and traditions of philosophy.
Philogagging: an introduction -- Metaphysics -- Logic -- Epistemology -- Ethics -- Philosophy of religion -- Existentialism -- Philosophy of language -- Social and political philosophy -- Relativity -- Meta-philosophy -- Summa time : a conclusion -- Final exam -- Great moments in the history of philosophy.
Originally published: New York : Abrams Image, 2007.
Includes bibliographical references (p. 203-205) and index.
Adult.
Adult
Keywords: Philosophy; Philosophy -- Humor; Philosophy; Philosophy -- Humor